Investigation of ball burnishing process using vibration and acoustic emission sensors. Issue 1 (October 2021) - Fernandez, I; Velazquez, E; Marques, J; Lluma, J; Jerez, R; Travieso, J A
Abstract: In this paper, a ball burnishing tool mounted in a CNC lathe is characterized. This tool may work as vibration assisted ball-burnishing tool and in conventional way. The characterization consists of acoustic emission measurements in both burnishing processes, and vibration measurements with tri-axial accelerometers. The acoustic emission measurements permit to investigate if any kind of damage is produced in the material by the burnishing process. An operational deflexion shape exercise has been performed with the vibration measurements. This permits to investigate the movement of the tool during the burnishing process and to evaluate the rigidity of the tool.